DOMINASI BUDAYA K-POP MELALUI KONTEN DANCE CHALLENGE TIKTOK: ANALISIS KRITIS MEDIASCAPE ARJUN APPADURAI - Nandhita Intan Dwi Iskandar; Nisya Maharani; Rifma Ghulam Dzaljad (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Globalization is a phenomenon that influences various aspects of modern society, including social, economic, political, and cultural dimensions. This study aims to analyze the concept of globalization through the theoretical perspectives of Anthony Giddens, Zygmunt Bauman, and Ulrich Beck. The research method employs a qualitative approach using literature studies from various scientific sources. The results show that Anthony Giddens views globalization as the intensification of worldwide social relations, Zygmunt Bauman emphasizes the concept of liquid modernity that creates social uncertainty, while Ulrich Beck interprets globalization through the concept of risk society emerging from modernity development. These three theories indicate that globalization not only brings progress but also creates complex social challenges for contemporary society.